Preparation of magnetic mesoporous silica composite for the solid‐phase microextraction of diazinon and malathion before their determination by high‐performance liquid chromatography. Issue 8 (7th March 2017) - Bazmandegan‐Shamili, Alireza; Haji Shabani, Ali Mohammad; Dadfarnia, Shayessteh; Rohani Moghadam, Masoud; Saeidi, Mahboubeh
Abstract : A novel magnetic mesoporous silica material was synthesized and used as the sorbent for the magnetic solid‐phase microextraction of diazinon and malathion before their quantification by high‐performance liquid chromatography with UV detection. The sorbent was synthesized by a surfactant‐templated one‐pot sol–gel procedure using SiO2 ‐coated Fe3 O4 as the magnetic support, cetyltrimethylammonium bromide as the template and tetraethyl orthosilicate as the silicon source. The characteristics of the prepared sorbent were investigated using Fourier transform infrared spectroscopy, scanning electron microscopy, and X‐ray diffraction. The sorbent exhibited a high maximum adsorption capacity of 19.2 and 9.4 mg/g for diazinon and malathion, respectively. The parameters affecting the microextraction were optimized by the MultiSimplex method. Under the optimized conditions, the calibration graphs were linear in the concentration ranges of 0.3–50.0 and 0.5–50 μg/L with the limits of detection of 0.09 and 0.14 μg/L for diazinon and malathion, respectively. The relative standard deviations ( n = 5) at a concentration level of 10.0 μg/L of analytes were less than 2.5 and 4% for intra and interday, respectively. The developed method was successfully used for the determination of diazinon and malathion in apple, tomato, cucumber, tap water, and well water samples.